Peringatan Pintu Belum Tertutup Menggunakan Sensor Magnetik (Reed Switch) dan ESP32 - Dani, Sutha (Computer Journal, 2026)
Forgetting to close a door may seem like a small thing, but it can cause security issues and reduce comfort levels in homes and workplaces. To address this issue, researchers created a system that automatically detects door status. The system uses a Reed Switch magnetic sensor to check whether a door is open or closed, and uses an ESP32 module to process the data and control the output. The design process included circuit construction, programming the ESP32, and testing how well the sensor responds at different distances from the magnet. When the door is opened, the Reed Switch sends a signal to the ESP32, which then triggers a buzzer alarm. Tests showed that the system works in real time with fast response and good stability under various door movement conditions. The device continued to operate smoothly during long tests of up to 12 hours continuously. Experimental results showed that the sensor works very accurately without much noise interference, while the ESP32 executes its logic state stably even when affected by other environmental factors such as vibration and temperature changes. The system has a simple design, low cost, and uncomplicated installation, making it suitable for homes, offices, or other places that require an automatic reminder of a door being left open. This prototype can also be upgraded with Wi-Fi in the future to enable notifications to be sent remotely via a mobile app. The research shows that the combination of the Reed Switch and the ESP32 can effectively improve security by reducing user errors in everyday activities.